2010
DOI: 10.1007/s00381-010-1301-0
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive and social functioning in children and adolescents after the removal of craniopharyngioma

Abstract: Despite normal intellectual abilities and relatively good physical condition, children after removal of craniopharyngioma experience many difficulties in everyday life regarding social relationships, emotion control and learning. The analogy between the above-mentioned symptoms and symptoms observed in patients after infantile damage in the frontal area leads to an observation that, apart from endocrine disorders, damage to the frontal lobe caused by the growth of tumour and operational intervention is of cruc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
48
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(54 citation statements)
references
References 15 publications
4
48
0
1
Order By: Relevance
“…Neurocognitive dysfunction, including memory deficits (14,(59)(60)(61)(62)(63), has been described as an important contributor to the increased morbidity among CP patients. Problems with concentration, memory and executive function potentially affecting professional occupation and school performance have received more attention in recent years (8,9,14,62). Studies have shown that up to 50% of CP patients have psychosocial impairment on long-term follow-up (14), and up to one-quarter of patients are unable to work in their previous occupation or they are behind in school (9).…”
Section: Neurocognitive Functionmentioning
confidence: 99%
“…Neurocognitive dysfunction, including memory deficits (14,(59)(60)(61)(62)(63), has been described as an important contributor to the increased morbidity among CP patients. Problems with concentration, memory and executive function potentially affecting professional occupation and school performance have received more attention in recent years (8,9,14,62). Studies have shown that up to 50% of CP patients have psychosocial impairment on long-term follow-up (14), and up to one-quarter of patients are unable to work in their previous occupation or they are behind in school (9).…”
Section: Neurocognitive Functionmentioning
confidence: 99%
“…Long-term neurocognitive complications following treatment for childhood craniopharyngioma include cognitive problems, particularly those affecting executive function, attention, episodic memory, and working memory (Cavazzuti et al, 1983;Riva et al, 1998;Carpentieri et al, 2001;Poretti et al, 2004;Sands et al, 2005;Kiehna et al, 2006;Crom et al, 2010;Ondruch et al, 2011). In a recent report, Özyurt and coworkers provided first evidence that hypothalamic damage impacts on neural correlates of memory retrieval in medial prefrontal cortex, indicating a less efficient use of a prefrontal area involved in executive control processes.…”
Section: Quality Of Life Neurocognitive Outcome and Psychosocial Fumentioning
confidence: 94%
“…Neurocognitive deficits include memory disturbances, slower cognitive speed, attention problems, and behavioral instability (Cavazzuti et al, 1983;Colangelo et al, 1990;Carpentieri et al, 2001;Kiehna et al, 2006;Crom et al, 2010;Ondruch et al, 2011). While intact intellectual functioning has been reported in up to 82% of patients, visual memory is impaired despite normal visual-spatial abilities (Crom et al, 2010;Ondruch et al, 2011).…”
Section: Quality Of Life Neurocognitive Outcome and Psychosocial Fumentioning
confidence: 97%
See 1 more Smart Citation
“…[1] Approximately 4% of intracranial tumors are craniopharyngiomas [2][3][4]. However, it is the most common congenital and saddle region tumor in the children [5].…”
Section: Introductionmentioning
confidence: 99%